PERLINDUNGAN KONSUMEN DI ERA CHATBOT DAN AI: PENDEKATAN HUKUM BISNIS DIGITAL - I Gusti Ayu Widiadnyani; Kadek Frediandrika Adnantara (Universitas Mahendradatta, 2026)
The development of digital technology in the Industry 4.0 and Society 5.0 eras has brought significant changes in the interaction patterns between businesses and consumers. One of the rapidly developing innovations is the use of Artificial Intelligence (AI) and chatbots as a means of customer service in various sectors, including banking, e-commerce, and financial technology (fintech). Although this technology provides convenience and efficiency, its use also poses legal risks, such as misinformation, personal data leaks, and material and immaterial losses experienced by consumers. This study aims to analyze legal protection for consumers who interact with chatbot- and AI-based services through a normative legal approach with literature studies and analysis of laws and regulations. Some of the regulations reviewed include Law Number 8 of 1999 concerning Consumer Protection (UUPK), Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) in conjunction with Law Number 19 of 2016 Law No. 1 of 2024, Financial Services Authority (OJK) Regulation No. 6/POJK.07/2022, and the New Criminal Code (Law No. 1 of 2023). Research results show that current legal protection for consumers is still partial and does not specifically regulate the use of AI. AI is viewed merely as a tool, so responsibility remains with the business actors or corporations that operate it. The principles of strict liability and vicarious liability apply, where business actors remain fully responsible for losses incurred, even if errors occur in the AI system. Consumers have the right to compensation, personal data protection, and access to dispute resolution mechanisms, whether through negotiation, the Financial Services Authority (BPSK), the Financial Services Authority (OJK), or the courts. Specific regulations on AI are needed that address ethics, security, and clear accountability mechanisms for business actors. Thus, the development of AI technology can continue to support digital business innovation without neglecting consumer rights and protection in Indonesia's digital ecosystem.